1998
DOI: 10.2337/diabetes.47.9.1384
|View full text |Cite|
|
Sign up to set email alerts
|

Depot-related gene expression in human subcutaneous and omental adipocytes.

Abstract: Human omental adipocytes display a range of biochemical properties that distinguish them from adipocytes of subcutaneous origin. However, information about site-related gene expression in human fat cells is limited. We have previously demonstrated that leptin mRNA is markedly overexpressed in abdominal subcutaneous (SC) compared with omental (Om) adipocytes. To further investigate depot-specific differences in adipocyte gene expression, we have measured, in paired samples of isolated human adipocytes obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
208
9
32

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(280 citation statements)
references
References 0 publications
31
208
9
32
Order By: Relevance
“…Montague and colleagues show that expression of Tnfa and other genes varied among adipose tissue depots in humans. (51) Expression levels of both Adipoq, an adipokine that plays an important role in modulating insulin action and inhibiting gluconeogenesis, (52) and Slc2A4/Glut4 were increased in leptintreated mice, which is consistent with the improved insulin sensitivity of the mice treated with leptin in both this study and our previous one. As expected, expression of Lep (leptin) was decreased after both SC and ICV leptin treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Montague and colleagues show that expression of Tnfa and other genes varied among adipose tissue depots in humans. (51) Expression levels of both Adipoq, an adipokine that plays an important role in modulating insulin action and inhibiting gluconeogenesis, (52) and Slc2A4/Glut4 were increased in leptintreated mice, which is consistent with the improved insulin sensitivity of the mice treated with leptin in both this study and our previous one. As expected, expression of Lep (leptin) was decreased after both SC and ICV leptin treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Despite a very wide age range in our study material, we found no significant correlation between age and PPRE activity in the subcutaneous or intra-abdominal fat cells. It has earlier been shown that BMI and mRNA for PPARG are inversely related in subcutaneous fat cells [21]. However, we found no correlation between PPRE activity and BMI in either subcutaneous or intra-abdominal fat cells.…”
Section: Discussioncontrasting
confidence: 81%
“…This was confirmed by quantification of PPARG receptor in the two tissues, showing 55% higher levels of the receptor in omental fat cells. Furthermore, Montague et al have shown that the levels of mRNA for PPARG are not different in subcutaneous and omental human fat cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in gene expression of adipocyte-secreted molecules suggest that there are intrinsic fat depot-specific differences in the endocrine function of adipose tissue. Differentially expressed adipokines include leptin (Montague et al, 1998), plasminogen activator inhibitor-1 (Alessi et al, 1997), IL-6 (Fried et al, 1998) and visfatin (Fukuhara et al, 2005).…”
Section: Introductionmentioning
confidence: 99%